Analyzing the Influence of Accounting Information Quality on Debt Concentration: Moderating Effects of Financial Constraints and Managerial Risk Aversion - Mohsen Rashidi (بررسی‌های حسابداری و حسابرسی)
Objective: Enhancing the quality and reliability of accounting information augments the potential for sound decision-making and risk evaluation by external stakeholders, ultimately contributing to the rectification of shortcomings in debt contracts. The amount of borrowing from multiple sources varies greatly among companies. Large companies with high credit ratings tend to diversify into different types of debt, while small companies with low credit ratings tend to have fewer types of debt. To rationalize the constrained utilization of specific loan types, proponents highlight potential economic advantages, such as decreased bankruptcy costs, reduced expenses for information gathering, and incentives for creditors to minimize monitoring. In this article, the aim is to investigate debt concentration based on the informational dimension of accounting quality.Methods: The current research adopts a quantitative approach within the realm of positivist inquiry. This classification stems from the fact that the concepts under investigation objectively exist in the external world, and there is complete independence between the researcher and the subject matter. Given that this research methodology revolves around delineating actual relationships within existing data, and presenting them in the form of a model, the study is categorized within the domain of descriptive research. For this purpose, data related to 120 companies listed on the Tehran Stock Exchange from 2011 to 2020 were extracted, and the combined data regression model. The Tobit model was used to test research hypotheses. To calculate the information dimension of accounting quality, Lee et al.'s (2021) model was used, and the normalized Herfindahl-Hirschman Index (HHI) was used to calculate debt concentration.Results: The research results indicated that the information dimension of accounting quality leads to a change in debt concentration. Also, the results of the third and fourth hypotheses indicated the effect of financial constraint on the dispersion of financing. Finally, the fifth and sixth hypotheses showed the effectiveness of managers' risk-taking on the concentration and number of debts.Conclusion: The environment in which managers operate is constantly changing as a result of fluctuations in the interests of individuals. This change in interests leads to a re-evaluation of risk by managers. Violation of contractual obligations by companies leads to the reflection of bad news in prices. In essence, to regulate and safeguard prices and mitigate the risk of information asymmetry for creditors, company managers curtail their risk-taking. Simultaneously, to secure their job positions, they adopt approaches that consider the interests of creditors. In companies with high accounting information quality, there is a greater tendency to reduce dispersion and diversity in the debt structure. This approach of centralization is a function of the company's financial situation and managers' risk-taking. Financial constraints lead to a change in the behavior of creditors towards the company and reduce their willingness to provide credit.